2015
DOI: 10.1177/105268461502500207
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Structure and Agency: Exploring the Role of Teacher Leadership in Teacher Collaboration

Abstract: Building on York-Barr and Duke's (2004) conceptual framework for teacher leadership, this article explores teacher leadership as an informal influence that arises out of interactions and is exerted through group processes and norms. Through a 4-month qualitative study of two teacher teams’ work during structured teacher collaboration, we sought to understand how teachers’ informal action and interaction influence their colleagues’ sense of self-efficacy and motivation to engage in collaborative work. Given our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Rather, this kind of learning is more of a “socially distributed phenomena” that develops over time, among members of a group. As teachers gain efficacy, they must have opportunities to reflect on what they master in the context of structured collaboration (Szczesiul & Huizenga, 2015).…”
Section: New Evidence On How Teachers Learn To Leadmentioning
confidence: 99%
“…Rather, this kind of learning is more of a “socially distributed phenomena” that develops over time, among members of a group. As teachers gain efficacy, they must have opportunities to reflect on what they master in the context of structured collaboration (Szczesiul & Huizenga, 2015).…”
Section: New Evidence On How Teachers Learn To Leadmentioning
confidence: 99%
“…A national survey of teachers, found intensive coaching is relatively rare, and only 7 percent of teachers surveyed report that their schools have strong collaboration models (Gates Foundation, 2014). Professional development still remains quite "top down" and hierarchical while researchers point to the importance of peer influence in teacher learning as a "socially distributed phenomenon" (Papay, et al, 2016;Szczesiul & Huizenga, 2015).…”
Section: Significancementioning
confidence: 99%
“…Teachers acting in leadership roles within schools can create change through collaborative work that improves students' learning (Katzenmeyer & Moller, 2009; York‐Barr & Duke, 2004). Teacher learning and teacher leadership are connected, especially collaborative inquiry among teachers, which can facilitate teachers in developing as leaders (Darling‐Hammond et al., 2017; Szczesiul & Huizenga, 2015; Yow & Lotter, 2016). Recent research has found that schools in which teachers feel they have a voice in instructional and school‐based decisions, especially those concerning student discipline and school improvement issues, have higher student academic achievement (Ingersoll, 2018; Shen et al., 2020).…”
mentioning
confidence: 99%